Critically Analysing Plant-based Bioactives as Anti-inflammatory Agents: A molecular Phytopharmacology Perspective Coupled with Bibliometric Data - Riya Pal; Altamash Khan; Sinchan Das; Sanjay Kumar Bharti; Arjun Patra; Vivekananda Mandal (Bioactivities, 2025)
This study presents a critical, mechanistic, and bibliometric analysis of plant-derived bioactive compounds for the treatment of inflammation. From a molecular phytopharmacological perspective, this review critically examines the anti-inflammatory potential of key phytochemical classes, including polyphenols, alkaloids, glycosides, tannins, and essential oils, highlighting their ability to modulate cytokines and signalling pathways such as NF-κB, MAPK, and COX/LOX. Using the Scopus database (2020–2024); 17,129 publications were evaluated to identify global research trends, co-authorship networks, and journal participation. China and India demonstrated the highest research output, while Portugal, Turkey, and Italy showed notable international collaboration and influence. A preference for open-access publishing was also observed, enhancing visibility and citation impact. Integrating bibliometric and mechanistic insights, the analysis underscores a growing shift toward evidence-based and integrative approaches in phytochemical research. Overall, plant bioactives represent a promising, multi-targeted strategy for developing safer anti-inflammatory therapeutics.